2015
DOI: 10.1186/s13071-015-0863-9
|View full text |Cite
|
Sign up to set email alerts
|

Small mosquitoes, large implications: crowding and starvation affects gene expression and nutrient accumulation in Aedes aegypti

Abstract: BackgroundEnvironmental factors such as temperature, nutrient availability, and larval density determine the outcome of postembryonic development in mosquitoes. Suboptimal temperatures, crowding, and starvation during the larval phase reduce adult mosquito size, nutrient stores and affect vectorial capacity.MethodsIn this study we compared adult female Aedes aegypti, Rockefeller strain, raised under standard laboratory conditions (Large) with those raised under crowded and nutritionally deprived conditions (Sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 56 publications
4
60
0
Order By: Relevance
“…In fact, absent-nutrition caterpillars showed little, if any, inducible responses, especially when the fact that their immune genes are constitutively upregulated was taken into account (Figs 4 and 5). Food-deprived Drosophila (Becker et al, 2010) and mosquitoes (Aedes aegypti; Price et al, 2015) also show a similar shift towards a more constitutive expression of inducible antimicrobial genes (Becker et al, 2010), suggesting that this may be a common response in insects.…”
Section: Discussionmentioning
confidence: 96%
“…In fact, absent-nutrition caterpillars showed little, if any, inducible responses, especially when the fact that their immune genes are constitutively upregulated was taken into account (Figs 4 and 5). Food-deprived Drosophila (Becker et al, 2010) and mosquitoes (Aedes aegypti; Price et al, 2015) also show a similar shift towards a more constitutive expression of inducible antimicrobial genes (Becker et al, 2010), suggesting that this may be a common response in insects.…”
Section: Discussionmentioning
confidence: 96%
“…Drosophila melanogaster : Becker et al, 2010;Tsuzuki et al, 2012; mosquitoes (Aedes aegypti): Price et al, 2015; and M. sexta 5th instar caterpillars: Adamo et al, 2016a,b). Specific intracellular pathways induce antimicrobial peptide expression and production without the usual activation of pathogen recognition pathways (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Further, nutrient availability and daily temperature regimes can vary significantly among active breeding containers distributed in the same household area (Hemme et al, 2009). Despite shared genetic ancestry, larval stress has proven a critical influence on adult phenotype, which in turn is strikingly correlated with a suite of life history traits including vector competence (De Jesus and Reiskind, 2016; Honek, 1993; Mourya et al, 2004; Ponlawat and Harrington, 2007; Price et al, 2015; Schluter et al, 1991; Vantaux et al, 2016). In a previous study, our laboratory demonstrated the G × E influence of larval stress on adult body size (Schneider et al, 2011).…”
Section: Introductionmentioning
confidence: 99%